2016
DOI: 10.1002/2015jf003637
|View full text |Cite
|
Sign up to set email alerts
|

Flow structure and resistance over subaquaeous high‐ and low‐angle dunes

Abstract: A prominent control on the flow over subaqueous dunes is the slope of the downstream leeside. While previous work has focused on steep (~30°), asymmetric dunes with permanent flow separation, little is known about dunes with lower lee slope angles for which flow separation is absent or intermittent. Here we present a laboratory investigation where we systematically varied the dune lee slope, holding other geometric parameters and flow hydraulics constant, to explore effects on the turbulent flow field and flow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
91
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 72 publications
(112 citation statements)
references
References 92 publications
7
91
0
Order By: Relevance
“…Additionally, flow separation, reattachment, and reacceleration change the temporal distribution of near‐bed fluid velocities at any given distance along the bed form profile (Figure c). Instead of being a narrow distribution that is characterized fairly well by the mean, flow separation and acceleration over bed forms increase the dispersion of the fluid velocity distribution and shear stress distributions (Figure c; Emadzadeh & Cheng, ; Jovic & Driver, ; Kwoll et al, ; Le et al, ; Nelson et al, ). Due to greater dispersion, it is possible to have both a mean shear stress that is below the critical shear stress as well as events that exceed that same critical shear stress (Figure c).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, flow separation, reattachment, and reacceleration change the temporal distribution of near‐bed fluid velocities at any given distance along the bed form profile (Figure c). Instead of being a narrow distribution that is characterized fairly well by the mean, flow separation and acceleration over bed forms increase the dispersion of the fluid velocity distribution and shear stress distributions (Figure c; Emadzadeh & Cheng, ; Jovic & Driver, ; Kwoll et al, ; Le et al, ; Nelson et al, ). Due to greater dispersion, it is possible to have both a mean shear stress that is below the critical shear stress as well as events that exceed that same critical shear stress (Figure c).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a FSZ is also strongly related to the maximum angle of the slip face slope (Figure i). Lefebvre et al () and Kwoll et al () showed that over regular bedforms, the size of the flow separation increases with increasing slip face angle. In the present case, it is difficult to differentiate between the absence of flow separation and a shortening of the FSZ with decreasing maximum slip face angle.…”
Section: Río Paraná Bedformsmentioning
confidence: 99%
“…Based on numerical modeling of flow over triangular bedforms, Lefebvre and Winter () suggested that flow separation is permanent for slip face angles steeper than 11–18°, depending on bedform relative height (bedform height compared to water depth). From laboratory measurements of flow over fixed bedforms, Kwoll et al () concluded that a permanent flow separation exists only over slip face angles of 30°, and a small intermittent FSZ is present over bedforms with slip faces of 10° and 20°. These recent results based on systematic studies confirmed previous results indicating that flow separation is permanent for lee side slopes larger than 10–20° (Best & Kostaschuk, ; Kostaschuk & Villard, ; Paarlberg et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Lee side slopes of these low‐angle dunes are typically ≪30°, often ~10° (e.g., Kostaschuk and Villard, , ; Hendershot et al, ; Roden, ; Smith & McLean, ), and do not exhibit permanent flow separation. Instead, the flow recirculation region over low‐angle dunes is replaced by a zone of decelerated flow with intermittent separation (Best & Kostaschuk, ; Carling et al, ; Kwoll et al, ; Lefebvre & Winter, ; Roden, ; Smith & McLean, ). The generation mechanism for large‐scale CFS in the absence of permanent flow separation has not been identified, despite observations from deep rivers and estuaries that show significant transport of suspended sediment associated with CFS over low‐angle dunes (Hendershot et al, ; Kostaschuk, ; Kostaschuk & Villard, ; Kwoll et al, ; Smith & McLean, ).…”
Section: Introductionmentioning
confidence: 99%
“…Some recent advances have been made in laboratory investigations of flow over low‐angle dunes and negative steps with low step angle (Best, Kostaschuk, & Villard, ; Best & Kostaschuk, ; Kwoll et al, ; Motamedi et al, ; Motamedi, Afzalimehr, Harb, et al, ; Motamedi, Afzalimehr, Singh, et al, ; Ruck and Makiola, ; Sukhodolov, Fedele, & Rhoads, ). Ruck and Makiola () and Sukhodolov et al () documented wake formation and hence turbulence production downstream of low‐angle negative steps (10° and 15°) and dune lee slopes of 10°, respectively, in the absence of permanent flow separation.…”
Section: Introductionmentioning
confidence: 99%